2000
DOI: 10.1053/jhep.2000.19324
|View full text |Cite
|
Sign up to set email alerts
|

Incubation Phase of Acute Hepatitis B in Man: Dynamic of Cellular Immune Mechanisms

Abstract: After hepatitis B virus (HBV) infectionThe incubation period of a viral disease refers to the time between infection and the onset of symptoms, and has been believed to represent the phase of active viral replication before an effective host immune response. This period is generally long after infection with noncytopathic viruses such as hepatitis B virus (HBV), 1 in contrast to other viral diseases. [2][3][4] The development of symptoms, which may occur up to 6 months after HBV infection, 5 has been assumed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
316
1
1

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(347 citation statements)
references
References 28 publications
29
316
1
1
Order By: Relevance
“…Our findings indicate that CHB patients have T-cell failure. The same finding has also been demonstrated previously, namely, that the chronicity of HBV infection is caused by a deficiency in cellular immune function [16][17][18][19][20] , and hepatocyte damage is mainly caused by immunological injur y [21][22][23][24][25][26][27][28][29] . However, the mechanism has not been defined [5] .…”
Section: Figuresupporting
confidence: 76%
See 1 more Smart Citation
“…Our findings indicate that CHB patients have T-cell failure. The same finding has also been demonstrated previously, namely, that the chronicity of HBV infection is caused by a deficiency in cellular immune function [16][17][18][19][20] , and hepatocyte damage is mainly caused by immunological injur y [21][22][23][24][25][26][27][28][29] . However, the mechanism has not been defined [5] .…”
Section: Figuresupporting
confidence: 76%
“…Hepatocyte damage may also be correlated directly with T-cell failure, rather than through the load copies of viral replication. Previous studies have suggested that hepatocyte damage is mainly caused by immunological injury [9,[21][22][23][24][25][26][27][28][29][30] . HBV is a typical non-cytopathic virus that can induce tissue damage of variable severity by stimulating a protective immune response that can simultaneously cause damage and protection, by killing an intracellular virus through the destruction of virus-infected cells [5] .…”
Section: Figurementioning
confidence: 99%
“…During the natural course of HBV infection, patients with self-limited acute hepatitis B may develop strong virus-specific CD8 and CD4 T cell responses, although these T cell immune responses against the virus are insufficient to control infection in chronic hepatitis B (CHB) carriers (2)(3)(4). The mechanisms underlying this defect of specific T cell immunity have not yet been fully elucidated.…”
mentioning
confidence: 99%
“…Low or undetectable DNA levels were seen in acute hepatitis [3] , whereas HBV DNA levels became detectable during reactivation of chronic hepatitis [4] . Kumar et al [5] in their study showed a low level of HBV DNA (< 0.5 pg/mL) in about 96% of patients with acute infection, as opposed to 13% in those with exacerbation of chronic hepatitis.…”
Section: To the Editormentioning
confidence: 99%
“…Using these criteria for antiviral therapy as stated by the guidelines, only 20%-60% of hepatocellular carcinoma (HCC) patients and 27%-70% of patients who died of non-HCC were identified for antiviral therapy. If the criteria were broadened with baseline serum albumin 3.5 gm/dL or less or platelet counts of 130 000 mm 3 or less, 89%-100% of deaths from non-HCC liver-related complications and 96%-100% HCC patients would be identified for antiviral therapy.…”
Section: To the Editormentioning
confidence: 99%